Enhancement of a three phase induction motor performance by using a nonlinear inverse dynamics controller - Keream, Settar Subry (2017)
Decreasing the ripple torque in the induction motor has become a preoccupation of many researchers in recent years. It has many impacts on the effective performance of the induction motor (IM), increases efficiency, reduces losses and extends the life of its spare parts. As a result of the (IM)’s features which are robustness, economical, reliable and maintenance free, it is used in large-scale industrial applications. In general, when taking the induction motor performance, and the torque ripple into consideration, the impact is too significant to be ignored. Thus, this thesis focus on developing a new Nonlinear Inverse Dynamic (NID) method to control the three-phase induction motor. Three types of NID namely General Nonlinear Inverse Dynamic, Voltage Control Nonlinear Inverse Dynamic and Current Control Nonlinear Inverse Dynamic. These methods are based on field oriented with space vector pulse width modulation. The NID controller canceled a non-desirable response of the induction motor and enhanced the performance. This cancellation attempts by careful nonlinear algebraic equations. The mathematical model of induction motor and decoupling between two inputs were achieved. Then the desired new dynamic is derived from implementing the proposed NID technique that reserves some benefits such as fast torque control, minimum ripple torque, and fast speed response. The proposed methods were tested by 0.3 Kw IM and also tested with 100% uncertainty for stator and rotor resistances and 20% of mutual inductance. The high-performance minimum ripple torque operation of the closed-loop system was proved through simulation and experiment. The results are verified and proved that the proposed NID system achieves smaller torque ripple and faster torque response than the conventional feedback linearization control (FLC) and direct torque control (DTC) method and robust for parameters uncertainty. Whereas, several types of error analysis had been verified such as sensitivity error analysis, current errors analyses, controller model parameter error analysis, speed measurement error analysis, current measurement error analysis, and stability analysis. The experimental results are performed using programming torque device set as a load, the computer platform as the only interface to the user, the digital signal processor with model TMS320F28335 DSP chip as a controller board, inverter, DC power supply, encoder, and data acquisition systems. The reference speed is 40 Rad/Sec and load torque is 0.8 N.M are used. These, have all been successfully derived, analyzed, simulated, and practically implemented. It has been shown that the system closed-loop output error is equal to zero at all times and not just at steady state. Finally, the comparison of the proposed methods and other works have verified the objectives of the work. Also, the proposed method significantly reduced the torque ripple which is the major concerns of the classical hysteresis-based in DTC and FLC scheme and have an effect on the stator current distortion.